Red cell distribution width, other hematological parameters and atherogenic index of plasma in patients with clopidogrel and aspirin resistance - Ustundag Budak, Yasemin; Huysal, Kagan; Karadag Gecgel, Sanem; Ari, Hasan; Melek, Mehmet; Yavuz, Senol; Camci, Sencer; Karakus, Alper; Aktas, İbrahim; Ari, Selma (The European Research Journal, 2016)
Objective. Chronic inflammation might favour platelet hyperactivity, which leads to inter-individual variability in antiplatelet resistance. The aim of this study was to test the hypothesis that there is a relationship between some hematological parameters reported as measures of systemic inflammation, the atherogenic index of plasma (AIP), and antiplatelet responsiveness.Methods. This retrospective study included patients receiving aspirin (100 mg) and clopidogrel (75 mg) daily before and after stenting. Platelet inhibition was assessed using the VerifyNow P2Y12 point-of-care test. Resistance to antiplatelet therapy was defined as P2Y12 reactivity exceeding 240 units (for clopidogrel) or aspirin reaction units exceeding 550 units (for aspirin). The AIP was calculated as the logarithm of triglyceride/high density lipoprotein cholesterol. The white blood cell (WBC), platelet (P), neutrophil (N), and lymphocyte (L) counts, red cell distribution width (RDW), hemoglobin (Hb), plateletcrit, mean platelet volume (MPV), platelet distribution width, and N/L and P/L ratios were evaluated.Results. Of 232 patients (73% male; median age, 63 years; range, 38-87 years), 52 (22%) were aspirin resistant and 82 (35%) were clopidogrel resistant; 7.7% were both aspirin and clopidogrel resistant. Median RDW levels were significantly higher (14.4% [interquartile range (IQR) 3] vs. 13.9% [IQR 1.3]; p=0.01) and Hb levels significantly lower (12.0±1.6 g/dL vs. 13.2±1.7 g/dL; p0.05). Multivariate logistic regression showed that Hb (odds ratio [OR]=0.73; 95% confidence interval [CI], 0.60-0.88; p=0.001) and RDW (OR=1.26; 95% CI, 1.02-1.55; p=0.02) were independent predictors of clopidogrel resistance.Conclusion. Both RDW and Hb were independent variables associated with clopidogrel resistance, but antiplatelet resistance cannot be predicted based on other hematological parameters or AIP.